DEVELOPING LOCAL WISDOM BASED DIGITAL STORYTELLING THROUGH BLENDED LEARNING METHOD AS AN INNOVATIVE MEDIA FOR TEACHING WRITING AT EIGHT GRADE STUDENTS OF SMP NEGERI 2 SINGARAJA - Dewi, Komang Trisna (Institut Hindu Dharma Negeri Denpasar, 2019)
This research was a Research and Development (R&D) which aimed at developing local wisdom based digital storytelling through Blended Learning method as an innovative media for teaching writing at eighth grade students of SMP Negeri 2 Singaraja. The data were collected by using documentation technique, interview, observation, and questioner. The collected data were analyzed quantitatively to find out the mean score, in which the mean score was categorized based on the criterion referenced evaluation table. This research found that, (1) in developing local wisdom based digital storytelling through Blended Learning method required a chronologically steps, namely: observation, need analysis, designing prototype of the media, expert judgment, revising the product, field testing, analyzing the data and finalizing the final product, (2) the total of mean score of the questionnaire filled by the English teacher was 4.14, it indicated that the local wisdom based digital storytelling through Blended Learning method was categorized as excellent, and (3) furthermore, the result of the questionnaire filled by the students was 3.78, it represented that the implementation of local wisdom based digital storytelling through Blended Learning method could be categorized as good. The results of this study were highly expected can help both the teachers and the students in the process of teaching and learning writing narrative text.